Ben 10 : alien swarm - West, Tracey, 1965-; Cartoon Network (Television network) (New York, NY : Scholastic, 2009)
Fifteen-year-old Ben Tennyson straps on his Omnitrix, which allows him to morph into different aliens, gathers his pals Gwen and Kevin, and sets out to find his missing grandpa Max, encountering friends and foes along the way.
"Based on the new movie!"--Cover.
"Cartoon network"--Cover.
Includes promotional poster (col. ; 36 x 20 cm).
Keywords: Teenagers -- Juvenile fiction; Aliens -- Juvenile fiction; Fantasy -- Juvenile fiction; Adventure and adventurers -- Fiction